2021
DOI: 10.1002/lol2.10194
|View full text |Cite
|
Sign up to set email alerts
|

Lake browning generates a spatiotemporal mismatch between dissolved organic carbon and limiting nutrients

Abstract: The ecological effects of long-term increases in dissolved organic carbon (DOC) are poorly understood. One hypothesis, developed from surveys and short-term experiments, is that increases in DOC (also known as "browning") will increase productivity in low DOC systems due to associated increases in limiting nutrients, while productivity will decrease in high DOC lakes due to increased light limitation. A critical assumption of this hypothesis is that the ratio of nutrients or dissolved absorbance to DOC remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Across all of our lakes, DOC was moderately related to color ( r 2 = 0.42). We also observed that DOC was positively related to nutrient concentrations (TP ~ DOC, r 2 = 0.45), as has been reported in a continental study of lakes in the U.S. (Stetler et al 2021). Overall, our findings were concordant with DOC and nutrients being positively associated with algal production metrics, especially in low to intermediate DOC sites.…”
Section: Discussionsupporting
confidence: 88%
“…Across all of our lakes, DOC was moderately related to color ( r 2 = 0.42). We also observed that DOC was positively related to nutrient concentrations (TP ~ DOC, r 2 = 0.45), as has been reported in a continental study of lakes in the U.S. (Stetler et al 2021). Overall, our findings were concordant with DOC and nutrients being positively associated with algal production metrics, especially in low to intermediate DOC sites.…”
Section: Discussionsupporting
confidence: 88%
“…Phytoplankton communities responded to different N forms, especially in the presence of P additions, suggesting phytoplankton communities have flexibility in their nutrient demands and can capitalize on the DON pool across a range of nutrient conditions. In this region and others around the world, lakes are experiencing an increase in dissolved organic matter (“browning”; Williamson et al 2015; Stetler et al 2021) and increasing DON concentrations (Stetler et al 2021). Expanding on these results to understand how various N forms, both labile and refractory, might affect phytoplankton might prove crucial for predicting algal blooms and nutrient limitation and setting load limits in freshwater ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, differences in the direction and magnitude of trends across resources may signify shifts in aquatic nutrient limitation via changing N : P (Isles et al 2018) as well as a growing imbalance in the supply of organic energy vs. nutrients (e.g., DOC : inorganic N). These shifts and imbalances could constrain the growth of aquatic heterotrophs (Taylor and Townsend 2010) and regulate aquatic productivity (Stetler et al 2021).…”
mentioning
confidence: 99%